2018
DOI: 10.1159/000493013
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Thymic Stromal Lymphopoietin-Activated Dendritic Cells Promote Th2 Differentiation through the OX40 Ligand

Abstract: Objectives: Exosomes are extracellular vesicles released from various inflammatory cells, such as T cells, B cells, dendritic cells (DCs), and mast cells, which have been implicated in the modulation of immune response in asthma. This study aimed to investigate whether exosomes from DCs activated by thymic stromal lymphopoietin (TSLP) play a role in T-helper cell differentiation through the OX40 ligand (OX40L). Methods: Serum samples from patients with asthma were collected to measure the levels of OX40L, T-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…The first release of the exosome database included 58,330 circRNAs, 15,501 lncRNAs, and 18,333 mRNAs, which suggests a sophisticated genetic control system [13]. These functional RNAs can affect biological activities and modulate cellular events such as cell proliferation, apoptosis, differentiation, and immunoregulation [1416].…”
Section: Exosomesmentioning
confidence: 99%
“…The first release of the exosome database included 58,330 circRNAs, 15,501 lncRNAs, and 18,333 mRNAs, which suggests a sophisticated genetic control system [13]. These functional RNAs can affect biological activities and modulate cellular events such as cell proliferation, apoptosis, differentiation, and immunoregulation [1416].…”
Section: Exosomesmentioning
confidence: 99%
“…Exosomes contain various types of molecules, such as lipids, proteins, lipid rafts, mRNAs, miRNAs, and other non-coding RNAs, such as long non-coding RNAs (lncRNAs) (Zhang et al, 2015). Various cell types can release exosomes, such as reticulocytes (Pan and Johnstone, 1983;Diaz-Varela et al, 2018), dendritic cells (Morelli et al, 2004;Huang et al, 2019), B cells (Benjamin et al, 2019, mast cells (Xie et al, 2018), T cells , epithelial cells (Lv et al, 2019), and tumor cells (McAtee et al, 2019).…”
Section: Description Of Exosomesmentioning
confidence: 99%
“…Most knowledge on lung-resident DCs is based on the development of asthma, where they play a pivotal role in establishing an allergen-specific Th2 response in the airways after stimulation with epithelial alarmins (62). A recent study showed that DCs stimulated in vitro with the epithelial alarmin thymic stromal lymphopoietin secrete EVs expressing OX40L on their surface, via which they stimulate the proliferation of CD4 T cells and Th2 differentiation (63). Furthermore, EVs secreted by monocyte-derived DCs purified from human airways express HLA-DR, MHC-I molecules, CD63, CD86, and CD54, suggesting their potential to cross-present antigen-loaded MHC molecules mediating co-stimulation (21).…”
Section: Dendritic Cellsmentioning
confidence: 99%